Study of Selling Technique of Rubber Seed and Profit Analyze in Langkan Village, Banyuasin III Subdistrict, Banyuasin Regency. - Atika, Yeni; Iskandar, Sutarmo; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2015)
Study of Selling Technique of Rubber Seed and Profit Analyze in Langkan Village, Banyuasin III Subdistrict, Banyuasin Regency. The aim of this research is to describe about the selling technique of rubber seed in Langkan village, Banyuasin III subdistrict, Banyuasin regency. Analyzing the profit rate of rubber seed in Langkan village, Banyuasin III subdistrict, Banyuasin regency. Besides, this research has a benefit for the researcher in adding a knowledge and insight, giving an overview about the selling technique ofrubber seed, becoming a consideration and literature for the next researcher. The applied methods is a survey method and the applied sampling method in this research is a purposive method. In this research, the sample is taken amount to 16 cultivating farmers of 30 populations that the farmers who cultivate the rubber seed with land area of 0,5 – 2 Ha. The reason to take 16 farmers as sample is the amount of land area of the farmers as sample wider than the land of other farmers, while the data colleting method is an interviewmethod and the observation uses questionnaire to the farmers, the applied processing method is a approach of qualitative descriptive analysis and descriptive analysis with a mathematic approach. The result of this research indicates that the selling technique of rubber seed is the rubber seed in form ready to sell, with one way is a direct selling to CV. Bernas Noersery in Langkan village. While the profit rate that was obtained by the cultivating farmers in 2014 is 9,82/year at the price of rubber seed Rp. 3.500/polybag with a sellingvolume amount to 467.320 polybags of rubber seed.